Methods of Establishment and Crop Geometry on Rice (Oryza Sativa) Productivity Under Drip Irrigation - Kannan, S. Vallal; Ravikumar, V.; Sangeetha, Jebalin V V (European Journal of Applied Sciences, 2024)
A study was undertaken between 2020 and 2022 three years during the rabi season at Agricultural Engineering College and Research Institute in Kumulur with an aim to determining the optimal method of establishment, suitable paddy variety, and crop geometry with spacing for maximizing rice productivity in the standardized drip irrigation system. Experiment utilized a strip plot design, with two main establishment methods (direct seeding on raised beds and transplanting on flatbeds), three medium varieties (ADT 54, 'TKM 13', and 'CR 1009 sub-1') as subplot treatments, and three different spacing configurations and crop geometry at 20 x 10 cm (rectangle) conventional recommended spacing, 20 x 20 cm (square), and 25 x 25 cm (square) as sub-sub plot treatments. Plant height, total tillers count, productive tillers count, filled grains per panicle; test weight, grain yield, and straw yield were measured. Furthermore, an economic assessment encompassing cultivation expenses, gross income, net income, and Benefit-Cost Ratio (BCR) was carried out. Water-use efficiency was calculated by dividing the dry weight of grain yield (in kg/ha) by the total irrigation and rainfall (in ha. mm).Top of Form The findings indicated that direct seeding emerged as the superior method for establishing drip-irrigated rice cultivation. The most suitable combination treatment for achieving the growth and yield factors, highest grain yield (6080 kg/ha), net income (Rs. 64059/ha), benefit-cost ratio of 2.37, and enhanced water use efficiency (6.61 kg.ha-mm-1) involved direct-seeded rice on raised beds using a medium-duration variety with a spacing of 20x20cm with other recommended agronomic practices.This approach aims to improve both crop and water efficiency amid constraints in water availability.